2003
DOI: 10.1177/004051750307300102
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional and Physical Properties of Cotton/Spandex Single Jersey Fabrics

Abstract: In this study, the dimensional and physical properties of cotton/spandex single jersey fabrics are investigated and the results compared with fabrics knitted from otton alone. The loop length and amount of spandex are usted to determine the dimensions and properties of the knits. It is apparent that as the amount of spandex increases loop length values remain nearly the same and the course and wale spacing values decrease. Further more, because spandex-containing fabrics tend to tighter, the weight and thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 3 publications
3
52
0
5
Order By: Relevance
“…In other words, they are more or less independent of yarn and fabric parameters [2,4,5,9]. Hence, CO/SP single jersey structures gave lower intercepts than CO structures in three relaxation stages, which implied that CO/SP single jersey structures could reach a more stable and quickly relaxed state than CO structures, as given by other previous works [1,2,4,5]. The reason for this would be that due to their yarn elastic recovery properties, stitch shape changes quickly becoming a stable state with minimum yarn energy level.…”
Section: Course and Wale Spacingsupporting
confidence: 55%
See 3 more Smart Citations
“…In other words, they are more or less independent of yarn and fabric parameters [2,4,5,9]. Hence, CO/SP single jersey structures gave lower intercepts than CO structures in three relaxation stages, which implied that CO/SP single jersey structures could reach a more stable and quickly relaxed state than CO structures, as given by other previous works [1,2,4,5]. The reason for this would be that due to their yarn elastic recovery properties, stitch shape changes quickly becoming a stable state with minimum yarn energy level.…”
Section: Course and Wale Spacingsupporting
confidence: 55%
“…The reason for this would be that due to their yarn elastic recovery properties, stitch shape changes quickly becoming a stable state with minimum yarn energy level. Further, we have found that in considering the fabrics with same tightness factors, loop length variations at three relaxation stages were mostly below 3 % for both CO/SP and CO single jersey structures [1]. Thus, Table 4 gives the increasing percentages (%) of CPC and WPC values between relaxation treatments.…”
Section: Course and Wale Spacingmentioning
confidence: 81%
See 2 more Smart Citations
“…Other woks [15][16][17][18][19][20][21] have studied the effect of some single factors on comfort stretch properties. These properties are influenced by the finishing treatment, the amount of elastane, yarn count, yarn twist, yarn composition, fabric's structure and the operating parameters (gauge, loop length, ….…”
Section: Introductionmentioning
confidence: 99%